Cabinet Immunity in Canada: The Legal Black Hole - Campagnolo, Yan (McGill Law Journal / Revue de droit de McGill, 2017)
Fifteen years ago, in Babcock v. Canada (A.G.), the Supreme Court of Canada held that section 39 of the Canada Evidence Act, which deprives judges of the power to inspect and order the production of Cabinet confidences in litigation, did not offend the rule of law and the provisions of the Constitution. The aim of this article is to revisit this controversial ruling and challenge the Supreme Court’s reasoning. The first part seeks to demonstrate that the Supreme Court adopted a very thin conception of the rule of law in its jurisprudence, a conception which is of limited use as a normative framework to assess the legality of statutory provisions. To that end, the author turns to the thicker theory of law as justification which insists upon the requirements of fairness, transparency, and accountability. Pursuant to the theory of law as justification, an executive decision to exclude relevant evidence in litigation must comply with two requirements: it must be made following a fair decision-making process; and it must be subject to meaningful judicial review. The second part seeks to demonstrate that section 39 does not comply with these requirements. The decision-making process established by Parliament under section 39 is procedurally unfair, in violation of paragraph 2(e) of the Canadian Bill of Rights, because: the identity of the final decision-maker—a minister or the Clerk of the Privy Council—gives rise to a reasonable apprehension of bias; and the decision-maker is not required to properly justify his or her decision to exclude relevant evidence. In addition, section 39 infringes the core, or inherent, jurisdiction and powers of provincial superior courts, in violation of section 96 of the Constitution Act, 1867, as it unduly limits their authority to: control the admissibility of evidence in litigation; and review the legality of executive action. As a result of these flaws, the author argues that section 39 is an unlawful privative clause, a form of legal black hole, which offends the rule of law and the provisions of the Constitution.